التخطيط السياحي والتنمية السياحية - هرمز نور الدين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر التخطيط السياحي من أهم أدوات التنمية السياحية المعاصرة، التي تهدف إلى زيادة الدخل الفردي الحقيقي والقومي، وإلى تنمية حضارية شاملة لكافة المقومات الطبيعية والإنسانية والمادية في البلاد . ومن هنا فالتخطيط السياحي يعتبر ضرورة من ضرورات التنمية المستدامة الرشيدة الذي يمكن الدول خصوصا النامية منها من أن تواجه المنافسة في السوق السياحية الدولية. وبالتالي فإن تخطيط التنمية السياحية يعتبر جزءاً لا يتجزأ من خطة التنمية الاقتصادية والاجتماعية الذي يقتضي إلزام كافة الوزارات والأقاليم والأجهزة والإدارات الحكومية وغير الحكومية بتنفيذ السياسة التنموية السياحية (برنامج عمل مشترك). وبناء على ما تقدم تناول البحث بالترتيب أهم الأفكار التي تخدم الموضوع وفقا لما يلي: 1- مفهوم وتعريف التخطيط السياحي، أهميته، أهدافه. 2- خصائص التخطيط السياحي الجيد، ومستوياته. 3- مفهوم التنمية السياحية ومكوناتها، عناصرها، أهدافها، أشكالها. 4- مراحل إعداد خطة التنمية السياحية. 5- النتائج والتوصيات. Tourist planning is considered one of the most important tools of contemporary tourist development, aiming at increasing the real individual and national income, and for an overall civilized development that includes all natural, human and material resources of a nation. Consequently, tourist planning is regarded as a necessity for a wise and sustainable development that enables countries, especially developing ones, to face competition in the international tourism market. Hence, planning tourist development is considered an integral part of a social and economic development plan. All ministries, regions, apparatuses, governmental and non- governmental administrations should be obliged to implement the tourist development policy (joint-action program). Depending on the above-mentioned points, this paper has studied the following issues that serve the goals of the subject: -1The concept, definition, importance and goals of tourist planning -2Characteristics and levels of good tourism planning -3The concept, components, elements, goals and forms of tourist development -4Stages of preparing a tourist development plan -5Results and recommendations